2022
DOI: 10.14349/sumapsi.2022.v29.n1.4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of soccer and futsal players: A systematic review

Abstract: Introduction: The present systematic review aimed to compile the information available in the literature having to do with sport psychology regarding futsal and soccer players, in order to identify which psychological constructs are being investigated in these athletes and by means of which instruments and analysis techniques. Method: The search was carried out in the APA (PsycINFO), EBSCO (SportDiscus), PubMed, Web of Science, Scielo, Science Direct, Scopus, BVS and EMBASE databases, with the following descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…No differences were found in pre-match confidence or attention according to playing position, even when considering the outcome of the match. Previous research that has analyzed the psychological determinants of performance in futsal female players is scarce [ 10 ], but the results previously found are contrary to those of the present research since they showed that the pivots showed lower self-confidence and stress control compared to the rest of the players [ 27 ]. A possible explanation for the results found in terms of confidence is that Alvarez-Kurogi’s [ 27 ] research was carried out with promising young futsal players under 16 and 19 years of age; this is a stage in which sports performance is associated with the achievement of specific results [ 40 ], such as scoring effectiveness in the case of the pivots, and could be a factor to consider since the pivots in the present research were the ones with the most shots on goal compared to the rest of the players.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No differences were found in pre-match confidence or attention according to playing position, even when considering the outcome of the match. Previous research that has analyzed the psychological determinants of performance in futsal female players is scarce [ 10 ], but the results previously found are contrary to those of the present research since they showed that the pivots showed lower self-confidence and stress control compared to the rest of the players [ 27 ]. A possible explanation for the results found in terms of confidence is that Alvarez-Kurogi’s [ 27 ] research was carried out with promising young futsal players under 16 and 19 years of age; this is a stage in which sports performance is associated with the achievement of specific results [ 40 ], such as scoring effectiveness in the case of the pivots, and could be a factor to consider since the pivots in the present research were the ones with the most shots on goal compared to the rest of the players.…”
Section: Discussioncontrasting
confidence: 99%
“…However, physical demands are not the only relevant factors in the performance of futsal players since before, during and after the matches there are numerous psychological variables acting as determinants, such as group cohesion, perfectionism, motivation, satisfaction, leadership style or burnout [ 10 ]. These variables are interrelated since group cohesion is fundamental in a sport in which interpersonal relationships are established for the achievement of a common goal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of match attendance, media attention, salaries, and sponsorship, high-level and elite female football has lagged far behind that of their male counterparts ( FIFPRO, 2020 ). During the past 20 years, however, there have been positive developments in most of these areas, in addition to a growing body of research concerning female players ( Kirkendall, 2020 ), although this is not comparable to the amount of research conducted on male football players ( Kryger et al, 2021 ; Alves et al, 2022 ). The most prevalent research areas in the field of women’s football have been related to sports medicine, followed by physiology and sociology (society, patterns of social relationships, social interaction, and culture; Kryger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%